Studi Pemikiran Zakiyah Daradjat dalam Pendidikan Islam di Indonesia - Fahmi, Putri Firdaus; Aula, Fitria Faradina Kafa; Prasetyo, Dony Agus; Fatimah, Siti; Khoir, Mulyanto Abdullah (Lembaga Yasin AlSys, 2026)
This study examines the thought of Zakiyah Daradjat in the context of Islamic education in Indonesia using a qualitative descriptive method with a literature study approach. It focuses on her main ideas regarding the nature and aims of Islamic education, which she formulates as efforts to nurture human beings to become pious servants of Allah in all aspects of life—actions, thoughts, and feelings. She emphasizes that the foundations of Islamic education rest on the Al-Qur’an, As-Sunnah, and Ijtihad, and she positions the family, school, and society as the environments as well as the parties responsible for the educational process. The findings show that Zakiyah Daradjat’s contribution to Islamic education in Indonesia is manifested in two principal roles. First, as an educator and psychologist who devoted considerable attention to mental health, particularly in relation to adolescent issues. Second, as a bureaucrat and reformer of Islamic education who was directly involved in educational practice and policy formulation through strategic positions in government agencies and Islamic educational institutions. These contributions make Zakiyah Daradjat’s thought remain relevant and significant for the development of Islamic education in Indonesia to the present day.